2018
DOI: 10.1016/j.injury.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Closed incision negative pressure therapy decreases complications after periprosthetic fracture surgery around the hip and knee

Abstract: Our findings suggest that ciNPT may reduce wound complications, SSIs, and reoperations in patients undergoing lower extremity periprosthetic fracture surgery. This is the first study to investigate ciNPT as a treatment for periprosthetic fracture surgery, and has the potential to change the postoperative management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…30,31 Although this infection rate is higher than those reported for index THR, deep surgical site infection rates between 4.4 and 25% are reported in people treated for periprosthetic femoral fractures. [32][33][34][35] Possible explanations for the high infection rate could be due to the development of resistance to prophylactically administered cephalexin, extensive soft tissue dissection, prolonged surgical time, fracture associated trauma to surrounding tissues or the presence of preexisting implants. 30,35 Femoral fracture revision was performed without entering the hip and with a stitched-in impervious stockinettes to minimize prosthesis infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Although this infection rate is higher than those reported for index THR, deep surgical site infection rates between 4.4 and 25% are reported in people treated for periprosthetic femoral fractures. [32][33][34][35] Possible explanations for the high infection rate could be due to the development of resistance to prophylactically administered cephalexin, extensive soft tissue dissection, prolonged surgical time, fracture associated trauma to surrounding tissues or the presence of preexisting implants. 30,35 Femoral fracture revision was performed without entering the hip and with a stitched-in impervious stockinettes to minimize prosthesis infection.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] Possible explanations for the high infection rate could be due to the development of resistance to prophylactically administered cephalexin, extensive soft tissue dissection, prolonged surgical time, fracture associated trauma to surrounding tissues or the presence of preexisting implants. 30,35 Femoral fracture revision was performed without entering the hip and with a stitched-in impervious stockinettes to minimize prosthesis infection. Collection of exit cultures for revision procedures may be beneficial in these higher risk cases.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search identified 12 RCTs, a majority of which reported reduced SSI rates, reduced readmission rates, and reduced reoperation rates. Six of the non-RCT, comparative studies identified also reported reduced rates of SSIs, readmissions, and reoperations [20][21][22][23][24][25]. However, these studies examined a wide range of patients, with a variety of comorbidities, undergoing different surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The successful application of ciNPT on clean, closed wounds has been reported in a broad spectrum of patients and operative interventions resulting in positive clinical results in a majority of the RCTs identified in the literature search ( Table 2) [11][12][13][14][15][16][17][18][19]. Similarly, rates of SSIs, surgical site complications, readmissions, and/or reoperations were reduced in patients receiving ciNPT compared to historical control populations [20][21][22][23][24][25].…”
Section: Literature Searchmentioning
confidence: 95%
“…Negative-pressure wound therapy (NPWT) is a form of adjuvant treatment that has been gaining attention recently in the orthopedic literature. Although its use is well established in other areas of medicine and orthopedics, especially in cases of trauma with severe lesions in soft parts and exposed fractures, 4 - 6 its use in the field of primary arthroplasties and prosthetic revision surgeries is still not well established. Studies of cases of periprosthetic fractures after knee and hip and ankle arthroplasties have demonstrated the benefit of using this type of therapy.…”
Section: Introductionmentioning
confidence: 99%